Vaccination Intention and Behavior of the General Public in China: Cross-sectional Survey and Moderated Mediation Model Analysis - Liuqing Yang; Lili Ji; Qiang Wang; Yan Xu; Guoping Yang; Tingting Cui; Naiyang Shi; Lin Zhu; Shixin Xiu; Hui Jin; Shiqi Zhen (JMIR Publications, 2022)
BackgroundPromoting vaccination and eliminating vaccine hesitancy are key measures for controlling vaccine-preventable diseases. ObjectiveWe aimed to understand the beliefs surrounding and drivers of vaccination behavior, and their relationships with and influence on vaccination intention and practices. MethodsWe conducted a web-based survey in 31 provinces in mainland China from May 24, 2021 to June 15, 2021, with questions pertaining to vaccination in 5 dimensions: attitude, subjective norms, perceived behavioral control, intention, and behavior. We performed hierarchical regression analysis and structural equation modeling based on the theory of planned behavior-in which, the variables attitude, subjective norms, and intention each affect the variable intention; the variable intention mediates the relationships of attitude and subjective norms with behavior, and the variable perceived behavioral control moderates the strength of this mediation-to test the validity of the theoretical framework. ResultsA total of 9924 participants, aged 18 to 59 years, were included in this study. Vaccination intention mediated the relationships of attitude and subjective norms with vaccination behavior. The indirect effect of attitude on vaccination behavior was 0.164 and that of subjective norms was 0.255, and the difference was statistically significant (P<.001). The moderated mediation analysis further indicated that perceived behavioral control would affect the mediation when used as moderator, and the interaction terms for attitude (β=-0.052, P<.001) and subjective norms (β=-0.028, P=.006) with perceived behavioral control were significant. ConclusionsSubjective norms have stronger positive influences on vaccination practices than attitudes. Perceived behavioral control, as a moderator, has a substitution relationship with attitudes and subjective norms and weakens their positive effects on vaccination behavior.